Development and Prospect of Satellite 5G Technology - Lijun ZHAI; Shuming PAN; Chunting WANG (天地一体化信息网络)
With the development of new broadband satellite communication constellation, the fusion of satellite communication and 5G has become a hot spot in the communication industry.The current status of the development of satellite 5G was summarized, and the work achievements of 3GPP, ITU, SaT5G and other international standard development organizations were introduced.On the basis, the overall architecture of satellite 5G network was proposed, the research and development were introduced such as networking under the condition of satellite dynamic topology, multi band satellite ground integration waveform design, multiple access to satellite IoT terminal, radio resource management and interference coordination.In addition, the feasibility of new technologies such as OTFS, nonorthogonal multiple access and interference coordination of NGSO and GSO based on spectrum sensing were explored.Finally, the development of the 6G phase of integrated satellite and terrestrial networks was presented.